Rada Główna Episkopatu Polski wobec opozycji przedsierpniowej (1976–1981) - Łatka, Rafał (Pamięć i Sprawiedliwość, 2017)
In the above analysis, I have discussed the attitude of the Main Council of the Polish Episcopate towards the pre-August opposition. The approach of the leading body of the Polish Church to the opposition groups that originated in 1976–1977 has not been the topic of a separate and comprehensive study. The former part of the article outlines the increasing social importance of the Church in the 1970s and the role of that institution during the 1976 strikes. The introductory section is followed by the presentation of Primate Wyszyński’s and the most important Polish bishops’ attitudes towards opposition groups that originated in the latter half of the 1970s. The author focused on the position on the issue taken by the members of the Main Council as the most important decision-making body in the Polish Church after 1945. This is followed by a descriptionof the Episcopate’s opinion on ordinary clergy’s cooperation with the pre-August opposition in order to highlight the Council member’s stance on the opposition more. A separate fragment of the analysis is devoted to the discussion of the bishop’s attitude towards the risk of “politicisation” of academic ministries. It is particularly important due to the fact that the origin of certain opposition organisations can be seen in the activity of specific ministries. The next part of the article shows the attitude of the Council members towards the role of the opposition during the first papal pilgrimage. The final section outlines how the most important hierarchs of the Church felt about the role of the pre-August opposition during the legal existence of the “Solidarity” with particular attention to the circles related to the former Workers’ Defence Committee, which the members of the Main Council of the Episcopate were most passionate about.